Detection and characterization of triamcinolone acetonide metabolites in human urine by liquid chromatography/tandem mass spectrometry after intramuscular administration. (1st July 2014) - Matabosch, Xavier; Pozo, Oscar J.; Papaseit, Esther; Farré, Magí; Marcos, Josep; Segura, Jordi; Ventura, Rosa
Abstract : RATIONALE: Glucocorticosteroids are prohibited in sports when used by systemic administrations (e.g. intramuscular, IM), whereas they are allowed using other ways of administration. Strategies to discriminate between administrations routes have to be developed by doping control laboratories. For this reason, the metabolism of triamcinolone acetonide (TA), one of the most used glucocorticosteroids, was studied using liquid chromatography coupled to tandem mass spectrometry (LC/MS/MS). METHODS: Urine samples obtained after IM administration of TA were analyzed using two sample treatments: (a) hydrolysis with β‐glucuronidase enzymes and liquid‐liquid extraction under alkaline conditions, and (b) liquid‐liquid extraction under acidic conditions. The extracts were analyzed by LC/MS/MS. RESULTS: TA, commercially available metabolites (6β‐hydroxytriamcinolone acetonide, 6β‐OH‐TA, and triamcinolone), and their C20‐reduced derivatives showed characteristic fragmentation behavior. Besides common product ions and neutral losses for corticosteroids containing fluorine, additional characteristic neutral losses (58 Da, loss of acetone; 44 Da, loss of acetaldehyde) were observed in positive electrospray ionization. Based on that behavior, two complementary approaches were applied to detect TA metabolites: (a) open detection by precursor ion and neutral loss scan methods and (b) targeted detection by selected reaction monitoring methods (SRM) containing theoretical ion transitions of the potential metabolites. Two main compounds, TA and 6β‐OH‐TA, and nine minor potential metabolites, were detected by open screening methods. Using SRM, two additional metabolites were detected. Some of the metabolites were characterized using reference standards and, for the rest of metabolites, feasible structures were proposed based on mass spectrometric data. CONCLUSIONS: Metabolites resulting from hydroxylation in C‐6, oxidation of the 11‐hydroxyl group, reduction of the Δ 4 double bond and oxidation of the side chain were detected. Some of them have not been previously described. Excretion profiles of the detected metabolites after IM administration are presented. Copyright © 2014 John Wiley & Sons, Ltd.